Development of a carbon-11 PET radiotracer for imaging TRPC5 in the brain. Issue 22 (22nd May 2019) - Yu, Yanbo; Liang, Qianwa; Liu, Hui; Luo, Zonghua; Hu, Hongzheng; Perlmutter, Joel S.; Tu, Zhude
Abstract : A potent carbon-11 PET tracer targeting TRPC5 was radiosynthesized successfully and the preliminary evaluation in rodents and a nonhuman primate was performed. Abstract : The transient receptor potential channel subfamily member 5 (TRPC5) is a calcium permeable cation channel widely expressed in the brain. Accumulating evidence indicates that it plays a crucial role in psychiatric disorders including depression and anxiety. Positron emission tomography (PET) combined with a TRPC5 specific radioligand may provide a unique tool to investigate the functions of TRPC5 in animal disease models to guide drug development targeting TRPC5. To develop a TRPC5 PET radiotracer, the potent TRPC5 inhibitorHC608 was chosen for C-11 radiosynthesis through the N -demethyl amide precursor7 reacting with [ 11 C]methyl iodide. Under optimized conditions, [ 11 C]HC608 was achieved with good radiochemical yield (25 ± 5%), high chemical and radiochemical purity (>99%), and high specific activity (204–377 GBq μmol −1, decay corrected to the end of bombardment, EOB). The in vitro autoradiography study revealed that [ 11 C]HC608 specifically binds to TRPC5. Moreover, initial in vivo evaluation of [ 11 C]HC608 performed in rodents and the microPET study in the brain of non-human primates further demonstrated that [ 11 C]HC608 was able to penetrate the blood brain barrier and sufficiently accumulate in the brain. These results suggest that [ 11 C]HC608 has the potential to be a PET tracer for imaging TRPC5 in vivo .